Implementasi Metode RAD pada Sistem Informasi Manajemen Penelitian, Pengabdian Masyarakat dan Luaran - Siska Narulita; Sekarlangit; Ahmad Nugroho; M. Zakki Abdillah (Fakultas Teknik Universitas Hamzanwadi, 2025)
Higher education institutions frequently struggle to manage research, community service, and output data. Manual data and information management is prone to mistakes. It is challenging for leaders and stakeholders to monitor and evaluate performance. This study intends to address these issues by offering a platform that meets the needs of the Community Service Research Institute (LPPM), leaders, and stakeholders. The primary features produced are statistics on research, service, and output data, as well as report generating automation. This study employs RAD to create the system. The system developed has been declared functional based on the results of blackbox testing with equivalent partitions. According to the 91% usability testing estimate, users are pleased with the information system built, and the system is simple to use. This system's specific benefits and potential implications include improved data management efficiency, consolidated data access, accreditation and reporting support, and higher institutional reputation